ضغوط العمل ومستوى أداء العاملين في المستشفيات الجامعية: دراسة تطبيقية باستخدام تقنية تحليل (الأهمية – الأداء) (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف البحث إلى تحديد العلاقة بين ضغوط العمل ومستوى أداء العاملين في المستشفيات الجامعية، واستنتاج الاستراتيجيات الملائمة للتخفيف من حدة ضغوط العمل. وقد طُبق البحث على عينة مكونة من 181 مبحوث من العاملين في مستشفيات التعليم العالي (الأسد الجامعي، التوليد وأمراض النساء) في مدينة دمشق.تم جمع البيانات باستخدام الاستبانة لقياس مفاهيم ضغوط العمل وأداء العاملين للعينة موضوع البحث. وقد استُخدمت تقنية تحليل (الأهمية– الأداء) (Importance- Performance) Analysis للرد على أسئلة البحث.توصل البحث إلى النتائج التالية:1. إن عوامل مثل (الجنس، نوع العمل، طبيعة العمل، العمر، عدد سنوات الخبرة، المؤهل العلمي) تلعب دوراً هاماً في مستوى الضغوط التي يتعرض لها العاملون في المشافي الجامعية.2. الحالة الاجتماعية (أعزب أو متزوج) للمبحوثين ليس لها دور في مستوى الضغوط التي يتعرضون لها.3. توجد علاقة ارتباط إيجابية ذات دلالة بين المستوى الكلي لأداء الفرد ومستوى الضغوط الناجمة عن الأبعاد التالية (السيطرة والتحكم، التأثير على القرارات، وضوح الدور).4. توجد علاقة ارتباط سالبة ذات دلالة بين المستوى الكلي لأداء الفرد ومستوى الضغوط الناجمة عن الأبعاد التالية (صراع الدور، متطلبات وعبء العمل).5. تمكين المرؤوسين من حيث إشراكهم في الاجتماعات التي تتعلق بتطوير الأعمال، وكذلك إشراكهم في القرارات التي تؤثر على الأعمال والمهام المناطة بهم.The study aims to determine the relationship between the job stress and the task performance of employees in the university hospitals, and determine the appropriate strategies to reduce the job stress. The study was applied on a sample of 181 workers in Higher Education hospitals (Al-Assad University Hospital, Obstetrics and Gynecology Hospital) in Damascus city.Data were collected through using a questionnaire to measure the stress job and the task performance for the employees in the sample of the study. Analysis (Importance- Performance) was used to answer the questions of the study.The study gives us the following results:1. The factors (such as gender, type of work, the nature of work, age, number of years of experience and educational qualification) have a big effect at the stress job for the workers in the university hospitals.2. Marital status (single or married) of the Researched workers does not have any effect at the stress job for the workers in the university hospitals.3. There is a positive correlation between the level of the task performance of the worker and the level of the stress job that caused by the following factors (Command and Control, Influence on Decisions and Clarity of the Role).4. There is a negative correlation between the level of the task performance of the worker and the level of the stress job that caused by the following factors (role conflict, requirements and workload).5. Enable of the subordinates to participate on the meetings that related to developing the job, as well as involving them in decisions that effect on their work and tasks.